Strategi Digital Marketing dalam Meningkatkan Penjualan Produk Lokal Daintys Handmade - Siti Nur Amanah; Lingga Yuliana (Master Manajemen, 2025)
This study discusses the digital marketing strategy implemented by Daintys Handmade, a local brand engaged in handicrafts (handmade) such as bags and accessories. The purpose of this study is to analyze the digital marketing strategy implemented by Daintys Handmade in its sales. This study uses qualitative descriptive research and interviews with the owner of Daintys Handmade. The results of the discussion show that a well-planned digital marketing strategy can increase sales volume and strengthen the position of local brands in the market. The digital marketing strategy implemented by Daintys Handmade, such as utilizing various marketplaces (Instagram, Shopee, Tiktok, Whatsapp Business), promotions through discounts, giveaways, endorsements, and digital advertising have proven effective in increasing sales volume.